Advanced TypeScript programming projects : build 9 different apps with TypeScript 3 and JavaScript frameworks such as Angular, React, and Vue - O'Hanlon, Peter (Packt Publishing, Limited, 2019)
Advanced TypeScript 3.0 Projects is a complete resource filled with a wide range of web-based projects to help you in advancing with the latest TypeScript features and ECMAScript standards.